NEGOTIATING SOCIAL IDENTITY IN URBAN SOCIAL SPACES - Sagidulla G. S. (Theoretical Hypotheses and Empirical Results, 2025)
This article examines the process of negotiating social identity in urban social spaces, using the city of Almaty as a post-Soviet metropolitan context. The study addresses the growing need to understand how social identities are constructed, contested, and reconfigured under conditions of rapid urbanization, socio-cultural diversification, and spatial transformation. The aim of the article is to systematically analyze and synthesize contemporary scholarly literature on social identity negotiation in urban environments, with particular attention to theoretical, conceptual, and empirical approaches relevant to Almaty. The study is based on a structured literature review of peer-reviewed international and regional publications indexed in major academic databases. Through thematic coding and comparative analysis, the research identifies key dimensions of identity negotiation, including urban social space, public realms, symbolic boundaries, institutional participation, and generational dynamics. The findings demonstrate that social identity in urban environments is a dynamic and relational process shaped by everyday interactions, spatial configurations, and governance frameworks. The analysis shows that, in the case of Almaty, ethnic Kazakh identity is not eroded by urban life but is actively reconstructed through the intersection of ethnic, civic, and urban forms of belonging. By integrating global theoretical perspectives with context-sensitive insights, the article contributes to urban sociology and identity studies and provides a conceptual foundation for future empirical research on social identity, social cohesion, and urban transformation in post-Soviet cities.